2018
DOI: 10.1021/acsami.7b17439
|View full text |Cite
|
Sign up to set email alerts
|

Giant Negative Piezoresistive Effect in Diamond-like Carbon and Diamond-like Carbon-Based Nickel Nanocomposite Films Deposited by Reactive Magnetron Sputtering of Ni Target

Abstract: Piezoresistive properties of hydrogenated diamond-like carbon (DLC) and DLC-based nickel nanocomposite (DLC:Ni) films were studied in the range of low concentration of nickel nanoparticles. The films were deposited by reactive high power pulsed magnetron sputtering (HIPIMS) of Ni target, and some samples were deposited by direct current (dc) reactive magnetron sputtering for comparison purposes. Raman scattering spectroscopy, energy-dispersive X-ray spectrometry (EDS), and X-ray photoelectron spectroscopy (XPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…6,7 Recently, high piezoresistive gauge factors (GF) up to 1200 and giant negative GF up to -3200 have been obtained for amorphous carbon films with a different atomic carbon bond structure. [8][9][10][11] Furthermore, the role of H atoms, the sp 3 /sp 2 ratio, and the sp 2 cluster size in piezoresistive behavior of a-C/a-C:H films has also been studied. Tibrewala et al reported that the presence of H atoms in the films could greatly affect their GF.…”
mentioning
confidence: 99%
“…6,7 Recently, high piezoresistive gauge factors (GF) up to 1200 and giant negative GF up to -3200 have been obtained for amorphous carbon films with a different atomic carbon bond structure. [8][9][10][11] Furthermore, the role of H atoms, the sp 3 /sp 2 ratio, and the sp 2 cluster size in piezoresistive behavior of a-C/a-C:H films has also been studied. Tibrewala et al reported that the presence of H atoms in the films could greatly affect their GF.…”
mentioning
confidence: 99%
“…Among them Nickel and graphite are also found to be strain sensitive material and they are used with other materials to enhance the piezo resistive nature of the overall compound [9], [14]- [16]. The effect of nickel particles in the composite enhances the piezo resistive effect of the compound [16]- [18] and the property is enhanced when there is change in temperature [19], [20]. In this paper, a composite of nickel nanoparticles and graphite is used as sensing material on a flexible substrate and the change in resistance for mechanical deformation is investigated and studied.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, the Si-based sensors could not meet the requirements of some special circumstances involving the harsh working conditions, such as automotive engines, geothermal, deep well-drilling, and aerospace, due to its inherent defect of the narrow band gap (1.12 eV). 8 Furthermore, various other novel candidates had also been explored for improving the piezoresistive performance, including MoS 2 membranes, 9 graphene, 10 ceramics, 11 diamond-like carbon, 12 providing a great opportunity for major breakthroughs in the development of outstanding pressure sensors. Nevertheless, these candidates still suffer from poor chemical stability and low sensitivity owing to their own inherent defects, which results in limiting the device integration and application in harsh working conditions.…”
Section: Introductionmentioning
confidence: 99%